A Porous and Interconnected Polypyrrole Film with High Conductivity and Ion Accessibility as Electrode for Flexible All‐Solid‐State Supercapacitors. Issue 21 (8th November 2019) - Mao, Jingwen; Liu, Congcong; Cheng, Chi; Zhang, Weimin; Liao, Xiao‐Zhen; Wang, Jiulin; Li, Linsen; Yang, Xiaowei; He, Yu‐Shi; Ma, Zi‐Feng
Abstract: Nanoporous electrodes with high electrical conductivity and good mechanical properties are attractive for high‐performance flexible supercapacitors. In this work, we report a flexible polypyrrole (PPy) film electrode synthesized by a modified versatile vapor‐phase polymerization (VPP) strategy. Differing from conventional VPP protocols that are likely to form smooth polymer films, it could easily engineer the PPy film with porous and interconnected structure by simply optimizing the concentration of oxidant and the polymerization time. The film electrode showed an exceptionally high electrical conductivity up to 94 S cm −1 . The unique porous PPy films constructed by interconnected electronic/ionic conductive networks achieved a specific capacitance of 494 F g −1 (corresponding to 836 mF cm −2 ) at a current density of 1 A g −1 . The fabricated all‐solid‐state supercapacitor device with the PPy electrodes exhibited a specific capacitance of 300 F g −1 at 1 A g −1 and a high energy density of 26.67 kW kg −1 . The high electrochemical performance and outstanding mechanical properties present the film electrode promising potential for flexible energy devices in various applications. Abstract : Electrode engineering : A highly conductive polypyrrole film with a porous and interconnected structure is prepared for use as electrode with super high conductivity and ion accessibility for all‐solid‐state supercapacitor.